Lincoln and Religion - Szasz, Ferenc Morton; Szasz, Margaret Connell (Carbondale : Southern Illinois University Press, 2014)
Abraham Lincoln's faith has commanded more broad-based attention than that of any other American president. Although he never joined a denomination, Baptists, Presbyterians, Quakers, Episcopalians, Disciples of Christ, Spiritualists, Jews, and even atheists claim the sixteenth president as one of their own. In this concise volume, Ferenc Morton Szasz and Margaret Connell Szasz offer both an accessible survey of the development of Lincoln's religious views and an informative launch pad for further academic inquiry. A singular key to Lincoln's personality, especially during the presidential.
IndexAuthor Biographies; Series Statement and Other Books in the Concise Lincoln Library; Back Cover
Description based upon print version of record.
Keywords: Lincoln, Abraham, 1809-1865 -- Religion; Presidents -- Religious life -- United States; United States -- Religion -- 19th century; Lincoln, Abraham, -- 1809-1865 -- Religion; Presidents -- Religious life -- United States; United States -- Religion -- 19th century; HISTORY / United States / State & Local / General; Electronic books